Clinical exome sequencing in early‐onset generalized dystonia and large‐scale resequencing follow‐up. Issue 4 (26th September 2016) - Zech, Michael; Boesch, Sylvia; Jochim, Angela; Weber, Sandrina; Meindl, Tobias; Schormair, Barbara; Wieland, Thomas; Lunetta, Christian; Sansone, Valeria; Messner, Michael; Mueller, Joerg; Ceballos‐Baumann, Andres; et al.
ABSTRACT: Background: Dystonia is clinically and genetically heterogeneous. Despite being a first‐line testing tool for heterogeneous inherited disorders, whole‐exome sequencing has not yet been evaluated in dystonia diagnostics. We set up a pilot study to address the yield of whole‐exome sequencing for early‐onset generalized dystonia, a disease subtype enriched for monogenic causation. Methods: Clinical whole‐exome sequencing coupled with bioinformatics analysis and detailed phenotyping of mutation carriers was performed on 16 consecutive cases with genetically undefined early‐onset generalized dystonia. Candidate pathogenic variants were validated and tested for cosegregation. The whole‐exome approach was complemented by analyzing 2 mutated yet unestablished causative genes in another 590 dystonia cases. Results: Whole‐exome sequencing detected clinically relevant mutations of known dystonia‐related genes in 6 generalized dystonia cases (37.5%), among whom 3 had novel variants. Reflecting locus heterogeneity, identified unique variants were distributed over 5 genes ( GCH1, THAP1, TOR1A, ANO3, ADCY5 ), of which only 1 ( ANO3 ) was mutated recurrently. Three genes ( GCH1, THAP1, TOR1A ) were associated with isolated generalized dystonia, whereas 2 ( ANO3, ADCY5 ) gave rise to combined dystonia‐myoclonus phenotypes. Follow‐up screening of ANO3 and ADCY5 revealed a set of distinct variants of interest, the pathogenicity of which was supported by bioinformatics testing and cosegregation work. Conclusions: Our study identified whole‐exome sequencing as an effective strategy for molecular diagnosis of early‐onset generalized dystonia and offers insights into the heterogeneous genetic architecture of this condition. Furthermore, it provides confirmatory evidence for a dystonia‐relevant role of ANO3 and ADCY5, both of which likely associate with a broader spectrum of dystonic expressions than previously thought. © 2016 International Parkinson and Movement Disorder Society.